The Relation between Helicobacter pylori Infection and Acute Bacterial Diarrhea in Children - Maryam Monajemzadeh; Ata Abbasi; Parin Tanzifi; Sahar Taba Taba Vakili; Heshmat Irani; Leila Kashi (Hindawi Limited, 2014)
Background. H. pylori infection leads to chronic gastritis in both children and adults. But recently, there are arising theories of its protective effect in diarrheal diseases. Aim. To explore the prevalence of H. pylori infection in children with bacterial diarrhea and compare it with healthy controls. Patients and Methods. Two matched groups consisted of 122 consecutive children, aged 24-72 months old, with acute bacterial diarrhea, who had Shigellosis (N=68) and Salmonellosis (N=54) as patients group and 204 healthy asymptomatic children as control group enrolled in this study. Results. The prevalence of H. pylori infection in healthy control children was significantly higher than in patients group, (odds ratio = 3.6, 95% CI: 1.33-9.5, P=0.007). In our study, only 2/54 Salmonella infected patients and 3/68 of Shigellosis had evidence of H. pylori infection, while normal control children had 27/204 infected individuals. Conclusion. H. pylori infection may play a protective role against bacterial diarrhea in children. So it is important to consider all of the positive and negative aspects of H. pylori infection before its eradication.